Effectiveness of video versus leaflet education on anemia prevention knowledge among young women: A comparative study - Rosyad, Shelly Rodliah; Wulandatika, Darmayanti; Fatimah, Siti (Universitas Aisyiyah Yogyakarta, 2024)
Iron deficiency Anemia is a national health problem that is associated with nutritional problems. Knowledge of anemia in adolescents is very necessary as a way of habituation to the consumption of FE tablets with one's own awareness. Through attractive Health Promotion media will increase health awareness by adolescents. Researchers want to aim to determine the difference in the effectiveness of education through video and leaflet media on the level of knowledge of young women about the Prevention of anemia in the city of banjarmasin. This study uses the type of quantitative research with quasi experiment design with pretest posttest approach non-equivalent control group design with pretest and posttest. Sampling technique is done by total sampling. The instruments in this study used questionnaires and statistical analysis using paired t-test to determine the level of knowledge of adolescent girls about anemia and independent t-test to determine the difference in the effectiveness of education through video and leaflet media on adolescent girls ' knowledge about anemia. The provision of education with video and leaflet media on young women's knowledge about anemia Prevention showed no significant difference. The results of this study indicate that the provision of education through leaflet media is slightly more effective than the provision of education through video media